Development of motor talents and nontalents in preschool age - An exploratory study - Krombholz, H.; Walla, P. (Cogent Psychology, 2018)
Using a 21-month longitudinal design, the development of physical characteristics (height, body weight, BMI, skinfold thickness), of physical skills (coordination, fitness, manual dexterity), and cognitive performance (concentration, verbal ability, intelligence) was investigated in 568 children aged 37-78 months. According to their performance in a Motor Test Battery, children were classified at the beginning of the study as high performing (percentile rank > 90 %), average performing (rank > 40 and <60), or underperforming (rank <10 %). Twenty-four children of the high, 54 children of the average, and 27 children of the underperforming groups took part at each of three trials (start, 10, and 21 months later). All groups improved their motor performance over trials. Children with high motor performance at the beginning of the study did perform better in coordination, fitness, and manual dexterity compared to average or low performing children at each trial. And they outperformed children with lower motor skills in concentration at each trial and in intelligence at the end of the study. Underperforming children had higher indices of body weight at each trial compared to high performing children and their health status was considered as less favorable; however, groups did not differ in standing height.